Deus ex nomine: Once more on the language myth and naïve religion - E. L. Berezovich; O. D. Surikova (Шаги)
This article draws upon the material of Russian cultural and linguistic tradition and analyses one particular phenomenon. In this phenomenon, a mythological character never existed in the folk belief system, but rather was generated by a linguistic sign or a text fragment. By their nature, the names of the characters studied in this paper derive from two types of verbal signs: 1) character names formed from regular lexical units — common nouns (роди́мчик, rodímchik ‘a seizure accompanied by convulsions and loss of consciousness’ > a character named Ро́дька, Ród’ka) or proper nouns (the forest Хéмерово, Khmerovo in the Arkhangelsk region > the forest spirit Хéмеровский, Khmerovskii); 2) character names that have a textual nature. The latter are constructions, or syntagms, that exist as an interconnected whole only within their “parent” text and then “migrate” outside it (Лель (Lel’), И́лия (Íliia) < song refrains алё-ле, ай люли (alio-le, ai liuli)). For a new character to appear, two stimuli are required: a linguistic stimulus proper (the existence of a name that “seeks” a content plane) and a cultural stimulus (a semiotically intense context: a situation associated with danger, prohibition, omen, aggression, magical practices). These stimuli are often combined, so the mythological nominative fund is almost guaranteed to renew constantly. The authors demonstrate that when “armchair” mythologists create characters based on linguistic stimuli, the same mechanisms are at work as those that function in “simple” folk tradition.